Economic Essentials of Islamic Microfinance and Importance in Poverty Reduction - Tursunov Anvar Sultonovich (Periodica Journal, 2023)
Poverty is one of the biggest challenges of the 21st century. More than three billion people in the world live in poverty. Muslim societies are far behind the rest of the world in tackling poverty. In Indonesia, which has the largest Muslim population in the world, more than half of the national population - about 129 million people - is poor or earns less than $ 2 a day. One of the main reasons for this is the limited access to financial services. In fact, the poor will not only need loans, but will also need a variety of banking services such as loans, savings, money transfers and insurance. As commercial banks specialize mainly in megacities, microfinance institutions come to the rescue. Microcredit organizations are also divided into two groups in terms of formation and operation. These are Traditional and Islamic microcredit organizations. The microcredit offered by traditional microfinance institutions contains an element of usury that is prohibited by Islamic Sharia, which prevents it from being used by the Muslim population and businesses in the country. This means that the establishment of Islamic microfinance institutions will play an important role in eradicating poverty in the country. Microfinance can be viewed in a narrow and broad sense. In the narrow sense, microfinance refers to the provision of small loans and leasing services. In a broad sense, microfinance includes a wide range of financial services, in addition to microcredit and microleasing, such as microfinance, microinsurance, money transfers, and consulting services. The provision of these services in accordance with the rules of Islamic Sharia is called Islamic microfinance. Unlike commercial banks, microfinance institutions have been established and are developing as a financial mechanism to serve low-income people. This article presents the economic necessity and importance of Islamic microfinance, as well as scientifically based proposals and recommendations for the establishment of the Islamic Microfinance Organization in Uzbekistan.
Keywords: Microfinance; usury; waqf; murabaha